ATURAN HUKUM BISNIS PERUSAHAAN DALAM SUDUT PANDANG KEBINEKAAN PANCASILA PADA ERA INDUSTRIAL 4.0 DI INDONESIA - Rashda Bintang Muhammad (PROSEDING, 2022)
The dynamics of Indonesia's development which is triggered by the development and progress of science and technology which is currently entering the industrial era 4.0 brings changes to the development of trade which can now be done electronically through digital electronics, artificial intelligence, big data, robotics. However, this technological development can be regarded as a double-edged sword, where on the one hand it can make a positive contribution to the improvement of welfare, progress and changes in human civilization which causes world relations without boundaries and this can lead to social change. , economy and culture significantly, increasing company investment, increasing productivity and quality at the same time can lead to a shift in conventional roles in the market, the emergence of competitive disputes, the emergence of illegal acts of business actors, disputes, the absence of the government's ability to regulate business models with new technology, and the emergence of social fragmentation that can increase economic risk. One thing is for sure that the industrial revolution 4.0 has come in our midst and we cannot possibly refuse or avoid it. This process will continue in the midst of ability or even inability, especially for the negative impacts that may be caused. Legal development carried out by the government must be a dynamic process following global demands in dealing with international contradictions and dilemmas faced by industrial society, especially in the trade/business sector. The challenge for the government in responding to the changes in the industrial era 4.0 revolution is to build a national law with an Indonesian personality, which is based on the philosophy and ideology of Pancasila. The development of laws based on Pancasila and the 1945 Constitution in the direction of a dignified civilized society in the face of various challenges and the influence of foreign ideologies Keyword : Industrial Era 4.0, Regulate Business Models, Pancasil, Business, Government.